An Analysis of Arabic Language Competence Among Madrasah Aliyah Graduates Based on the National Curriculum: a Descriptive Qualitative Study - Alia Salsabila; Khopipah Rohmatillah; M. Ramdan Alfarizi (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to determine the level of mastery of Arabic language competencies (listening, speaking, reading, and writing) among Madrasah Aliyah graduates based on the standards of the National Curriculum; the factors influencing their Arabic proficiency including aspects of instruction, teachers, learning environment, and curriculum; the alignment of Madrasah Aliyah graduates’ Arabic competencies with the competency requirements outlined in the National Curriculum; the challenges faced by graduates and institutions in achieving Arabic proficiency according to national standards; and the strategies that can be adopted to improve these outcomes. This research employs a descriptive qualitative approach to portray the Arabic language competencies of Madrasah Aliyah graduates based on the National Curriculum. Primary data were collected through interviews, observations, and documentation, while secondary data were obtained from curriculum documents and related literature. The analysis was conducted using the Miles & Huberman model, involving data reduction, data display, and conclusion drawing, ensuring structured and comprehensive findings. The study also provides a contextual overview of the Arabic learning process in Madrasah Aliyah. The results reveal that the Arabic language competence of Madrasah Aliyah graduates remains at a moderate level and has not yet met the standards of the National Curriculum, particularly in productive skills. The dominance of rote-based learning, limited communicative practice, lack of authentic media, and minimal exposure to Arabic in the learning environment are key factors contributing to the low achievement. Therefore, improving graduates' proficiency requires strengthening teacher competencies, implementing communicative methods, utilizing authentic media, and creating a consistent Arabic-language environment.